Sistem Pendukung Keputusan Penerimaan Staff Pengajar Menggunakan Simple Addictive Weighting Pada LPIA Dukuh Zamrud - Intan Cahya Syahfitri; Solikin Solikin (Journal of Students‘ Research in Computer Science, 2021)
Acceptance of teaching staff is an important process that aims to improve the productivity of a company's performance. The reception of teaching staff at the LPIA Hamlet Zamrud Bekasi still uses conventional methods so it requires a long time in the management process. Seeing this, it is necessary to have a computerized data management and decision making system for prospective teaching staff based on predetermined criteria namely micro teaching, teaching experience, recent education and age. In implementing a decision support system using the Simple Addictive Weighting (SAW) method, this method was chosen because in its calculation it can determine the weight values for each attribute, then proceed with the ranking process which will choose the best alternative from several alternatives based on the weights and criteria that have been set specify it. By using criteria to assist in the development and development of decision support systems for system development using the RAD (Rapid Application Development) method. Design and system analysis uses Unified Modeling Language (UML). By using the SAW method, the decision making for teaching staff acceptance becomes easier so that it speeds up the decision making process for teaching staff acceptance.   Keywords: Decision Support Systems, Rapid Application Development, Simple Additive Weighting, Teaching Staff, Unified Modeling Language.   Abstrak   Penerimaan staff pengajar merupakan suatu proses penting yang bertujuan untuk meningkatkan produktivitas kinerja suatu perusahaan. Penerimaan staff pengajar di  LPIA Dukuh Zamrud Bekasi masih menggunakan cara konvensional sehingga memerlukan waktu yang lama dalam proses pengelolaannya. Melihat hal tersebut, maka perlu adanya suatu sistem pengelolaan data dan pengambilan keputusan calon staff pengajar secara terkomputerisasi berdasarkan kriteria yang telah di tentukan yaitu micro teaching, pengalaman mengajar, pendidikan terakhir dan usia. Dalam penerapan sistem pendukung keputusan menggunakan metode Simple Addictive Weighting (SAW), metode ini dipilih karena dalam perhitungannya dapat menentukan nilai bobot untuk masing-masing atribut, kemudian dilanjutkan dengan proses ranking yang akan memilih alternatif terbaik dari beberapa alternatif berdasarkan bobot dan kriteria yang sudah di tentukan. Dengan menggunakan kriteria untuk membantu dalam pembangunan dan pengembangan sistem pendukung keputusan untuk pembangunan sistem menggunakan metode RAD (Rapid Application Development). Analisa desain dan sistem menggunakan Unified Modelling Language (UML). Dengan menggunakan metode SAW maka pengambilan keputusan penerimaan staff pengajar menjadi lebih mudah sehingga lebih mempercepat proses pengambilan keputusan penerimaan staff pengajar.   Kata kunci: Rapid Application Development, Simple Additive Weighting, Sistem Pendukung Keputusan, Staff Pengajar, Unified Modelling Language.